THE PROSKUROV MASSIF OF ALKALINE ROCKS (UKRAINIAN SHIELD): NEW GEOCHEMICAL DATABASE - Shnyukov, S.; Osypenko, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The current state of geological and geochemical information completeness on the alkaline rocks Proskurov massif (Dniester-Bug Region of Ukrainian Shield) has been reviewed in the article. Nowadays it classified as alkaline-altrabasic (carbonatite) formation together with Chernigovka carbonatite and Antonovsky massifs, Gorodnytska, Glumchanska and others intrusions. At the same time specific features (first of all geochemical) are noticed for Proskurov massif. However the ascertainment and explanation of their reasons are constrain by the lack of available geochemical information completeness, especially for trace elements. Based on new results of analytical investigations the new geochemical database has been formed. It includes main rock types (n = 304), represented in massif, and both qualitatively and quantitatively supplements data available for today. At this stage following problems were solved: (1) the generalization of existing information about massif, including geochemical; (2) new analytical data to supplement available ones was received; (3) the integration of obtained results into general database; (4) quality evaluation. Current control of the analytical data, that characterize considerably wider range of rock types, shows their applicability for following interpretation.